Deep-sea spider crabs of the family Epialtidae MacLeay, 1838, from PapuaNew Guinea, with a redefinition of Tunepugettia Ng, Komai & Sato, 2017, and descriptions of two new genera (Crustacea: Decapoda: Brachyura: Majoidea) - Lee, Bee Yan; de Forges, Bertrand Richer; Ng, Peter K. L. (Zootaxa, 2019)
The deep-water epialtid spider crab (superfamily Majoidea) material collected from recent French expeditions to Papua New Guinea (BIOPAPUA 2010, PAPUA NIUGINI 2012, MADEEP 2014, and KAVIENG 2014) was studied. In addition to several new records for the country, five new species of Oxypleurodon Miers, 1885, Rochinia A. Milne-Edwards, 1875, and Tunepugettia Ng, Komai & Sato, 2017, are described. The taxonomy of Tunepugettia is reappraised, and a new genus, Crocydocinus n. gen., is established, characterised by its smooth ambulatory legs and a distinct male first gonopod structure. Four species from the Bay of Bengal, Sumatra, and Réunion Island, currently placed in Rochinia and Tunepugettia are transferred to Crocydocinus n. gen. and four new species from Papua New Guinea, Philippines, and Vanuatu are described. A new genus, Neophrys n. gen., with one new species from Papua New Guinea, is established, and is characterised by the supraorbital eave being fused with the carapace and the poorly developed pre-orbital angle.